2013
DOI: 10.1093/gbe/evt152
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Survey on Genomic Variation, Expression Divergence, and Evolution in Two Contrasting Rice Genotypes under High Salinity Stress

Abstract: Expression profiling is one of the most important tools for dissecting biological functions of genes and the upregulation or downregulation of gene expression is sufficient for recreating phenotypic differences. Expression divergence of genes significantly contributes to phenotypic variations. However, little is known on the molecular basis of expression divergence and evolution among rice genotypes with contrasting phenotypes. In this study, we have implemented an integrative approach using bioinformatics and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…First, proper controls have to be analyzed, which also means evaluating the biomass of plants both in control and salt stress conditions, and controlling for the biomass in control conditions when necessary. It is common to use rice cultivar Pokkali as a salt‐tolerant reference in salinity stress experiments (Bhowmik et al , Jiang et al , Jain et al ). However Pokkali was one of the biggest plants, among the 56 different rice genotypes we analyzed under control conditions.…”
Section: Discussionmentioning
confidence: 99%
“…First, proper controls have to be analyzed, which also means evaluating the biomass of plants both in control and salt stress conditions, and controlling for the biomass in control conditions when necessary. It is common to use rice cultivar Pokkali as a salt‐tolerant reference in salinity stress experiments (Bhowmik et al , Jiang et al , Jain et al ). However Pokkali was one of the biggest plants, among the 56 different rice genotypes we analyzed under control conditions.…”
Section: Discussionmentioning
confidence: 99%
“…) from Pakistan, Nipponbare (Jiang et al. ) from Japan and Azucena (Awala et al ) from Philippines were previously reported as salt sensitive. Due to large number of genotypes, screening at germination stage was carried out in three sets of 33, 76 and 76 genotypes, whereas screening at vegetative stage was carried out in three sets of 70, 55 and 60.…”
Section: Methodsmentioning
confidence: 99%
“…Seeds of these genotypes were acquired from the Genebank of Plant Genetic Resources Institute, National Agricultural Research Centre, Islamabad, Pakistan, and other rice research institutes of Pakistan. Among the studied genotypes, Nona Bokra and Kharai Ganja (Khan et al 1987) and IR-6 from Pakistan were salt-tolerant (Gurmani et al 2006), whereas Basmati-370 (Yadav et al 2008) from Pakistan, Nipponbare (Jiang et al 2013) from Japan and Azucena (Awala et al 2010) from Philippines were previously reported as salt sensitive. Due to large number of genotypes, screening at germination stage was carried out in three sets of 33, 76 and 76 genotypes, whereas screening at vegetative stage was carried out in three sets of 70, 55 and 60.…”
Section: Plant Materialsmentioning
confidence: 96%
“…Of these, the affymetrix microarray platform is the most popular, and to date, 2741 array data have been produced and deposited at NCBI gene expression omnibus (GEO, http://www.ncbi.nlm.nih.gov/ geo/) (Barrett et al 2011). Of these, seven GEO data series have been produced to explore genome-wide transcriptional profiles in response to salt stress (Cotsaftis et al 2011;Jain et al 2007;Jiang et al 2013;Pandit et al 2010;Walia et al 2005Walia et al , 2007Walia et al , 2009. These experiments suggest a number of candidate genes for salt-stress responses in rice, but genes show conserved expression patterns in response to salt stress throughout genetic backgrounds and regional diversities have not been studied.…”
Section: Introductionmentioning
confidence: 99%